17 Predicting lateral ankle sprain in adolescent and collegiate athletes using functional tests. (12th October 2015) - Gribble, PA; Terada, M; Kosik, K; McCann, R; Pietrosimone, B; Quinlevan, M; Thomas, AC
Abstract : Background: Limited work suggests effective lateral ankle sprain (LAS) prediction with the star excursion balance test (SEBT) and Functional Movement Screen (FMS), but with small data sets using many different demographics. The utility of these tests needs to be confirmed in larger data sets. Objective: Establish LAS risk identification across multiple sport types using the SEBT and FMS. Design: Prospective cohort. Setting: Clinical. Patients (or participants): 1168 male and female high school and collegiate football, basketball, soccer or volleyball athletes. Interventions: Prior to beginning competitive seasons, participants completed the anterior (ANT), postero-medial (PM) and postero-lateral (PL) directions of the SEBT, normalised to leg length. An average composite (COMP) of the three normalised reaches also was calculated. Additionally, a modified FMS using the deep squat, lunge, hurdle-step and straight leg raise tests was assessed. Main outcome measurements: Certified athletic trainers recorded lower extremity injuries. As only LAS were examined, other lower extremity injury cases were removed, creating LAS (n = 157) and non-injured (n = 935) groups. Group differences of the whole sample, then within each sport, were compared using independent t-tests. For risk prediction, ROC curves were employed to create odds ratios for each dependent variable for the whole sample, and within each sport. Results: For the whole sample and for football, ANT and COMP scores were significantly lower in the LAS group (p < 0.005). In basketball, the COMP scores were significantly lower in the LAS group (p = 0.04). Using the overall sample, the largest odds ratio (1.55) was found for ANT. Football had the largest odds ratio among specific sport comparisons (2.83) from the ANT scores. Conclusions: The ANT test shows the most promise for LAS risk identification in athletes, especially football players. Continued work is needed to determine the most appropriate screening tool for LAS risk in specific groups of athletes.